The Advantages and Disadvantages of Fertigation - Mary Dixon; Guodong Liu (EDIS)
The purpose of this new 4-page article is to outline some of the major benefits and drawbacks a fertigation system may incur. The audience of this article includes county Extension faculty, students who are interested in crop production, growers, certified crop advisors, crop consultants, environmentalists, and policy makers in the agricultural sector. Written by Mary Dixon and Guodong Liu and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1442